Kontrol Diri dan Agresi : Tinjauan Meta-Analisis - Lita Widyo Hastuti (Faculty of Psychology Universitas Gadjah Mada, 2018)
Aggression brings adverse effects on individuals and the environment and often developsinto social problems. This meta-analysis study aimed to find out the correlation between self-control and aggression. The used samples based on 18 primary studies from 10 onlinejournals published in 2002 - 2017 which is found by searching on online database journal viawww.lib.ugm.ac.id. Two artifacts allowed for correction in this study are sampling errorand measurement error. The results of the analysis provided support for the hypothesis thatself-control had a negative correlation to aggression, therefore self-control inhibits the emerge of aggressive behavior.